Application of Geoinformation Systems for Assessment of Effective Integration of Renewable Energy Technologies in the Energy Sector of Ukraine - Ostapenko, Olga; Olczak, Piotr; Koval, Viktor; Hren, L. M.; Matuszewska, Dominika; Postupna, Olena (My University, 2022)
The scientific novelty of the results presented in this article is to substantiate and expand the possibilities of using global and local geographic information systems (GIS) to assess the potential of renewable energy sources in Ukraine. GIS analysis focused on key resource parameters can help identify territories for development of renewable energy sources and assess of their possible technical potential, as well as the possibility of effective integration of technologies for the use of renewable energy sources in the energy sector of Ukraine. In this paper the possibilities for using geographic information systems to assess the potential of renewable energy sources in Ukraine are analyzed. The possibility of using the Global Atlas of the International Renewable Energy Agency (IRENA) to support planning of technologies for the use of energy from biomass is analyzed. The data can point to large-scale programs and applications in relation to key parameters (quality resources, transmission distance, population density, terrain and site protection), helping identify additional areas for development of renewable energy sources and give an approximate assessment of technical potential. It is determined that the software products of IRENA are able to support national and regional planning of renewable energy technologies, help establish the viability of future renewable energy facilities and help project developers identify and analyze promising facilities for the implementation of technologies using renewable energy. The application of geographic information systems of Ukrainian web resources (“UA MAP”) for assessing the potential of renewable energy sources and energy efficiency in Ukraine is been analyzed. The scientific novelty of the results lies in applying global and local GIS for comprehensive assessment of the potential and effectiveness of the use of regional non-traditional and renewable energy resources on the territory of Ukraine. This makes it possible to assess the possibilities of generating additional electric and thermal power for the needs of the regions of Ukraine using non-traditional and renewable energy sources. A comprehensive methodology for the use of GIS is proposed for assessing the potential of nontraditional and renewable energy sources at the regional level in Ukraine, taking into account energy, environmental and socio-economic factors affecting the placement of non-traditional and renewable energy facilities.
Keywords: geoinformation systems; renewable energy sources; renewable energy technologies; Ukraine